Non-pharmacologic approaches to pain management - Wertheimer, Debra; Whiteford-Hadary (Firm) (Baltimore, Md. : VideoPress, 2002)
(Producer) Dr. Wertheimer talks with nursing assistants and residents in long-term care to consider non-pharmacological approaches to pain management. Discusses splinting, positioning, massage, and use of fans.
Content, Debra Wertheimer ; producer/writer, Susan Hadary
Presented by Debra Wertheimer
VHS
Keywords: Pain -- Therapy; Palliative Care -- methods